Cytotoxic chemotherapeutic agents and the EGFR-TKI osimertinib induce calreticulin exposure in non–small cell lung cancer. (May 2021) - Furukawa, Rie; Inoue, Hiroyuki; Yoneshima, Yasuto; Tsutsumi, Hirono; Iwama, Eiji; Ikematsu, Yuki; Ando, Nobuhisa; Shiraishi, Yoshimasa; Ota, Keiichi; Tanaka, Kentaro; Nakanishi, Yoichi; Okamoto, Isamu
Highlights: Cytotoxic chemotherapy and EGFR-TKI osimertinib induced prominent cell surface expression of CRT (ecto-CRT) in six NSCLC cell lines. Systemic anticancer therapies-triggered ecto-CRT expression in NSCLC cells was positively correlated with extent of apoptosis. Increased plasma levels of soluble CRT in advanced NSCLC patients treated with systemic anticancer therapies may serve as an indicator of ICD. Abstract: Objectives: Synergistic anticancer efficacy of combination treatment with immune checkpoint inhibitors (ICIs) and platinum-based chemotherapy in patients with advanced non–small cell lung cancer (NSCLC) may be attributable in part to the phenomenon of immunogenic cell death (ICD), which is characterized by the release of damage-associated molecular patterns (DAMPs) from dying tumor cells. The ability of cytotoxic chemotherapeutic agents and molecularly targeted drugs such as epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) to induce DAMPs during the treatment of NSCLC has remained unclear, however. Materials and methods: We investigated the ability of seven cytotoxic chemotherapeutic agents and the third-generation EGFR-TKI osimertinib to induce translocation of the DAMP calreticulin to the cell surface in multiple NSCLC cell lines. The plasma concentration of soluble CRT in advanced NSCLC patients treated with cytotoxic chemotherapy or osimertinib was measured. Results: Antimetabolites and microtubule inhibitors induced expression of CRT at the cell surface (ecto-CRT) to a greater extent than did platinum agents in six NSCLC cell lines, exhibiting higher up-regulation of phosphorylation of eukaryotic initiation factor-2α (eIF2α). Ecto-CRT expression was positively correlated with apoptosis induction in NSCLC cells treated with these various chemotherapeutic agents. The drug-induced up-regulation of ecto-CRT in NSCLC cells was attenuated by the pan-caspase inhibitor Z-VAD-FMK. Osimertinib similarly increased ecto-CRT expression in association with apoptosis induction in five EGFR -mutated NSCLC cell lines. Furthermore, the plasma concentration of soluble CRT in 16 NSCLC patients treated with single-agent pemetrexed or docetaxel and in nine EGFR -mutated NSCLC patients treated with osimertinib was increased after treatment onset. Conclusion: Our findings indicate that antimetabolites, microtubule inhibitors, and osimertinib are effective inducers both of CRT exposure in NSCLC cell lines and of soluble CRT release in patients with advanced NSCLC, suggesting that these agents might prove effective for promotion of antitumor immunity in combination immunotherapy.